Effect of Prognostic Guided Management of Patients With Acute Pulmonary Embolism According to the European Society of Cardiology Risk Stratification Model - Jiménez, David; Rodríguez, Carmen; Pintado, Beatriz; Pérez, Andrea; Jara-Palomares, Luis; López-Reyes, Raquel; Ruiz-Artacho, Pedro; García-Ortega, Alberto; Bikdeli, Behnood; Lobo, José Luis; , the IPEP investigators (Frontiers in Cardiovascular Medicine, 2022)
Background A recent trial showed that management driven by prognostic assessment was effective in reducing the length of stay (LOS) for acute stable pulmonary embolism (PE). The efficacy and safety of this strategy in each subgroup of risk stratification remains unknown. Methods We conducted a post-hoc analysis of the randomized IPEP study to evaluate the effect of a management strategy guided by early use of a prognostic pathway in the low- and intermediate-high risk subgroups defined by the European Society of Cardiology (ESC) model. These subgroups were retrospectively identified in the control arm. The primary outcome was LOS. The secondary outcomes were 30-day clinical outcomes. Results Of 249 patients assigned to the intervention group, 60 (24%) were classified as low-, and 30 (12%) as intermediate-high risk. Among 249 patients assigned to the control group, 66 (27%) were low-, and 13 (5%) intermediate-high risk. In the low-risk group, the mean LOS was 2.1 (±0.9) days in the intervention group and 5.3 (±2.9) days in the control group (P < 0.001). In this group, no significant differences were observed in 30-day readmissions (0% vs. 3.0%, respectively), all-cause (0% vs. 0%) and PE-related mortality rates (0% vs. 0%), or severe adverse events (0% vs. 1.5%). In the intermediate-high risk group, the mean LOS was 5.3 (±1.8) days in the intervention group and 6.5 (±2.5) days in the control group (P = 0.08). In this group, no significant differences were observed in 30-day readmissions (3.3% vs. 3.0%, respectively), all-cause (6.7% vs. 7.7%) and PE-related mortality rates (6.7% vs. 7.7%), or severe adverse events (16.7% vs. 15.4%). Conclusion The use of a prognostic assessment and management pathway was effective in reducing the LOS for acute PE without comprising safety across subgroups of risk stratification. Clinical Trial Registration [ClinicalTrials.gov], Identifier [NCT02733198].